(untitled) (University Heart Journal, 2011)
Diabetes mellitus (DM) itself increases the risk of Coronary Artery Disease (CAD) by 2-4 fold and in out country we are treating a good number of patients having CAD with DM. On the other hand several studies have reported increased risk of adverse outcomes following balloon angioplasty in diabetic cases. In this situation this study had been carried out at National Institute of Cardiovascular Diseases (NICVD) cath lab to determine the immediate procedural success & in-hospital adverse outcomes in this population. In our study 100 cases were enrolled. Out of which, 40 patients had type II DM & rest were non-diabetic. Diabetic patients were compared with non- diabetic and found no major difference between the two patient group except for a higher number of LCX (Left Circumflex) lesion in the non-diabetic (25% VS 35%, P value 0.038). The lone case of renal complication came from the diabetic group. No MACE (Major Adverse Cardiovascular or Cerebrovascular Events) or death was occur in this series. Angiographic, procedural and clinical success in diabetic was 97.5%, 97.5% & 95% respectively whereas 100% found in non-diabetic group at its all segment. But this results are statistically insignificant and P value is 0.4000 for angiographic success, 0.4000 for procedural success and 0.158 for clinical success. P value for hospital stays is also insignificant i.e. 0.250 (while p value of < 0.05 was considered significant). Therefore in the setting of diabetes mellitus the outcomes of the stenting procedure are quite encouraging. Key words: Coronary Stenting; Diabetic; Outcomes DOI: 10.3329/uhj.v6i1.7181 University Heart Journal Vol.6(1) 2010 pp.3-8